Heidelberg prinect digital solutions for print manufacturing workflows administration - Neroda T. (ТОВ «Друкарня Мадрид», 2024)
Automation of technological processes in printing orders preparation currently offers a wide range of digital solutions for organizing workflows. These solutions encompass fundamental aspects of prepress, press, and post -press order composing and are predominantly modular. Therefore, companies of commercial printing can use individual components within certain bundle workflow solution, depending on the coverage of needs and customer's target audience.
Keywords: print; administration